Beyond PaO2: Relationships between Indices of Pulmonary Oxygen Transfer in Hospitalized Adults Undergoing Blood Gas Testing - Feldman, MD, Mark; Rebel, BS, RRT, Denise (International Journal of Innovative Research in Medical Science, 2019)
The arterial partial pressure of oxygen in the arterial blood reveals limited information about pulmonary oxygen transfer. In 989 hospitalized patients undergoing arterial blood gas testing, we compared conventional indices of oxygen transfer: (1) P(A-a) O2 (A-a); (2) PaO2/PAO2 (a/A); and (3) the P/F ratio Nine hundred twenty-five of the patients were receiving supplemental oxygen therapy (FIO2 .24-1.00) and 65 were breathing room air. In patients receiving supplemental O2, the a/A ratio closely correlated with the P/F ratio (r = .98 to .99); the A-a O2 difference did not correlate as closely with the a/A ratio (r = -.77 to -.85) or with the P/F ratio (r = -.72 to -.80). In those breathing room air (FIO2 .21), the a/A ratio was closely and inversely correlated with the A-a difference (r= -.97 to -.98); correlations between the a/A and P/F ratios (r=.88 to .89) and between the P/F ratio and A-a O2 difference (r = -.78 to -.79) were less robust. We conclude that the a/A ratio is the preferred oxygen transfer parameter over the wide range of FIO2 levels encountered clinically.